Chemical and Nutritional Characterization of Seed Oil from Cucurbita maxima L. (var. Berrettina) Pumpkin - Montesano, Domenico (Foods, 2018)
Pumpkin (Cucurbita spp.) has received considerable attention in recent years because of the nutritional and health-protective value of seed oil. The nutritional composition of pumpkin native to central Italy, locally known as “Berrettina” (Cucurbita maxima L.), was evaluated. In particular, the lipid fraction of seed oil was characterized, and the triacylglycerol (TAG) was thoroughly studied by using a stereospecific procedure to obtain the intrapositional fatty acid composition of the three sn-positions of the glycerol backbone of TAG. Moreover, alkaline hydrolysis was carried out to study the main components of the unsaponifiable fraction, i.e., sterols and alcohols. It was observed that monounsaturated fatty acids and polyunsaturated fatty acids were the most abundant (41.7% and 37.2%, respectively) in Berrettina pumpkin seed oil, with high content of oleic and linoleic acid (41.4% and 37.0%, respectively). The main sterols of Berrettina pumpkin seed oil were Δ(7,22,25)-stigmastatrienol, Δ(7,25)-stigmastadienol, and spinasterol; with regard to the alcoholic fraction, triterpenic compounds were more abundant than aliphatic compounds (63.2% vs. 36.8%). The obtained data are useful to evaluate pumpkin seed oil from a nutritional point of view. The oil obtained from the seed could be used as a preservative and as a functional ingredient in different areas, e.g., cosmetics, foods, and nutraceuticals.